Evidence that central pathways that mediate defecation utilize ghrelin receptors but do not require endogenous ghrelin. Issue 15 (11th August 2017) - Pustovit, Ruslan V; Callaghan, Brid; Ringuet, Mitchell T; Kerr, Nicole F; Hunne, Billie; Smyth, Ian M; Pietra, Claudio; Furness, John B.
Abstract: In laboratory animals and in human, centrally penetrant ghrelin receptor agonists, given systemically or orally, cause defecation. Animal studies show that the effect is due to activation of ghrelin receptors in the spinal lumbosacral defecation centers. However, it is not known whether there is a physiological role of ghrelin or the ghrelin receptor in the control of defecation. Using immunohistochemistry and immunoassay, we detected and measured ghrelin in the stomach, but were unable to detect ghrelin by either method in the lumbosacral spinal cord, or other regions of the CNS. In rats in which the thoracic spinal cord was transected 5 weeks before, the effects of a ghrelin agonist on colorectal propulsion were significantly enhanced, but defecation caused by water avoidance stress (WAS) was reduced. In knockout rats that expressed no ghrelin and in wild‐type rats, WAS‐induced defecation was reduced by a ghrelin receptor antagonist, to similar extents. We conclude that the ghrelin receptors of the lumbosacral defecation centers have a physiological role in the control of defecation, but that their role is not dependent on ghrelin. This implies that a transmitter other than ghrelin engages the ghrelin receptor or a ghrelin receptor complex. Abstract : Centrally penetrant ghrelin receptor agonists act at the defecation centers in the spinal cord to trigger propulsive contractions of the colorectum and bowel emptying. However, although the ghrelin receptor is physiologically involved in defecation control, ghrelin is not.